LEARNING MEDIA TRAINING AND ASSISTANCE FOR BUDDHIST SUNDAY SCHOOL MANAGEMENT IN WONOGIRI REGENCY - Novianti, Novianti; Marjianto, Marjianto; Darma, Widia; Setyaningsih, Ratna; Putro, Adi Nugroho Susanto; Wulan, Ayuning (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
As part of implementing the Tri Dharma of Higher Education, the lecturer team in STAB Negeri Raden Wijaya Wonogiri, Central Java conducted community service activities in the form of "Training and Assistance for Buddhist Sunday School Management in Wonogiri Regency" (Efforts of Service Lecturers to Improve the Quality of SMB Management in Wonogiri Regency). The locations used as places to carry out community service activities are SMB Maitri Ratna in Giriwoyo District and SMB Dhamma Sasana in Slogohimo District. Based on observations in the field, it was found that Sunday school management had not been managed well and learning activities used monotonous material because Sunday school teachers had minimal training in both teaching and organizational management. This service activity is carried out by providing training and assistance to Sunday school coaches and teachers through 3 stages, namely observation, implementation, and ending with evaluation. The results of ongoing community service activities provide benefits, namely the preparation of Culla Sekha Sunday school learning plans, SMB teachers being able to use tangram media and interactive media in Sunday school activities, and the formation of the Maitri Ratna SMB management structure.